Disfungsi Endotel pada Perokok Pasif yang Sehat - Badai Tiksnadi; Augustine Purnomowati; M Rizky Akbar (The Indonesian Heart Association, 2012)
Introduction. Passive smoking may have a deleterious effect to cardiovascular system and subsequent enormous public health implication. The sidestream cigarette smoke suggest impaired endothelial production of nitrit oxide. Since endothelial dysfunction is an early feature of atherogenesis, early detection on this become important and hopefully can prevents the subsequent atherosclerlotic events. There were only few studies have assessed the effects of passive smoking to human arterial wall. The objective of this study was to detect endothelial dysfunction in healthy passive smokers young adults.Methods. We studied 80 healthy subjects 20 to 35 years old,which were divided into two groups, consist of 32 passive smokers and 48 subjects as controls. Passive smokers were defined as non-smokers who had been exposed to environmental tobacco smoke for at least one hour daily for three or more years. Endothelial function was measured by response of flow-mediatedÂ vasodilatation in brachial artery during reactive hyperemia.Result. There are no significant differences in baseline characteristics (age, sex and baseline diameter) between two groups. Flow-mediated dilatation response was significantlyÂ impaired in the passiveÂ smokers 8.7 (2.9) percent compared with 12.8 (6.7) percent in control subject, p =0.006.Conclusion. Passive smoking is associated with impairment of endothelium-dependent dilatation, suggesting early event in atherosclerosis.